BUILDING SAFER BEHAVIORS: THE RELATIONSHIP BETWEEN SELF-EFFICACY AND BURN INJURY AMONG STUDENTS - Fidiana Kurniawati; Selvia David Richard (Suluh Adiluhung Publisher (SAPub), 2026)
Burns are preventable injuries through safety behaviors supported by an individual's belief in their abilities (self-efficacy). This study aims to analyze the relationship between self-efficacy and burn prevention behaviors in college students. The study used a quantitative design with a cross-sectional approach. A sample of 36 students was selected using a purposive sampling technique. Data was collected using a self-efficacy questionnaire and burn prevention behaviors that had been tested for validity and reliability, then analyzed using Spearman’s Rho correlation test. The results showed that most respondents had moderate self-efficacy (41.7%) and good burn prevention behaviors (69.4%). Spearman Rank analysis showed a strong and significant relationship between self-efficacy and burn prevention behaviors (r = 0.701; p = 0.001). It was concluded that the higher the students' self-efficacy, the better the burn prevention behaviors they apply in their daily lives. Therefore, strengthening self-efficacy needs to be part of burn prevention safety education programs in higher education.